Antibiotic Delivery Strategies to Treat Skin Infections When Innate Antimicrobial Defense Fails - R. Smith; J. Russo; J. Fiegel; N. Brogden (MDPI AG, 2020)
The epidermal skin barrier protects the body from a host of daily challenges, providing protection against mechanical insults and the absorption of chemicals and xenobiotics. In addition to the physical barrier, the epidermis also presents an innate defense against microbial overgrowth. This is achieved through the presence of a diverse collection of microorganisms on the skin (the “microbiota”) that maintain a delicate balance with the host and play a significant role in overall human health. When the skin is wounded, the local tissue with a compromised barrier can become colonized and ultimately infected if bacterial growth overcomes the host response. Wound infections present an immense burden in healthcare costs and decreased quality of life for patients, and treatment becomes increasingly important because of the negative impact that infection has on slowing the rate of wound healing. In this review, we discuss specific challenges of treating wound infections and the advances in drug delivery platforms and formulations that are under development to improve topical delivery of antimicrobial treatments.